Analysis of the mechanical properties of wood-plastic composites based on agriculture chili pepper waste - Delia Julieta Valles-Rosales; Luis Alberto Rodríguez-Picón; Luis Carlos Méndez-González; Arturo del Valle-Carrasco; Haytham Alodan (Maderas: Ciencia y Tecnología, 2016)
In this study, a new composite material conception based on polypropylene (PP) and wood particles obtained from agricultural waste was investigated. Specifically, stalks and leafs of chili plants of the region of New Mexico, Texas, USA were used as a plant-based reinforcing material. For this, a design of experiments (DOE) is proposed considering different percentages of PP, wood, fire retardant, coupling agent and UV stabilizer, different mesh sizes are also considered. Samples were obtained using an extrusion molding machine. A statistical analysis is proposed to obtain the optimal percentages of the components considered in the fabrication of the samples in order to enhance the mechanical and morphologic properties of this new composite. Results show that the yield stress, breaking stress and ultimate tensile stress can be maximized with a proportion of 3 to 1 (63,75% PP and 21,25% wood fiber) of PP and wood fiber.